THE SENSUS FIDELIUM AND THE MAGISTERIUM FROM THE COUNCIL TO THE PRESENT DAY: MORALTHEOLOGICAL REFLECTIONS - Autiero, Antonio (Asian Horizons, 2015)
In the panorama of conciliar and post-conciliar thought also the category of sensus fidelium has undergone striking changes of understanding and emphasis. On the one hand they reproduce the relationship between sensus fidei and sensus fidelium, on the other hand they express implications at different levels of theological disciplines and practices in the Church. The essay tends to track the movements of thought and links related to the sensus fidelium, especially regarding moral theology. The sketch is oriented along two different Hermeneutics: the ecclesiological and the anthropological. The first one will explain the mutual influence between church model of competence and awareness of believers. The second one wants to revisit the importance of the category of experience in connection with to the foundation and validation of moral norms. The final look of the essay opens a space of interrogation about the epistemological status of this theological discipline and the profile of the moral theologian as subject of inspiration and reflection on the ethical phenomenon.